Refleksi Paradigma Ilmu Pengetahuan Bagi Pembangunan Hukum Pengadaan Tanah - Lego Karjoko; Zaidah Nur Rosidah; I Gusti Ayu Ketut Rahmi Handayani (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2019)
The purpose of this study is to explain the influence of the positivism paradigm in making land acquisition law and its application which is oriented towards formalism in Indonesia. This type of research is normative and prescriptive legal research, a paradigm that should be used to develop land acquisition law that can realize respect for land rights. To answer the research problem a concept approach is used with the analysis of the syllogism of deduction and interpretation. The paradigm of science as its major premise, while the regulation and application of land acquisition for public use as a minor premise. The results of this study are the positivism paradigm imbued with capitalism causing compensatory injustice and formal injustice in land acquisition for public use. Globalization, through international treaties, causes the importation of the laws of donor countries, which have a capitalist ideology to the Indonesian legal system, which has a family ideology. This harmonization problem if not resolved properly can cause injustice. To realize convergence, it is necessary to consider the use of realistic socio legal theory in land acquisition legal research. Keywords: Positivism, Realistic Legal Socio, Land Acquisition, Justice.